A Critical Analysis of the Bugis Wedding Tradition 'Passampo Siri - Jamal, Ridwan; Mitra, Asandi (IAIN Manado, 2024)
This paper examines the Passampo siri’ tradition (marriage of disgrace) in the Bugis community through paradigmatic analysis using the framework of Critical Theory. The research method used is a literature study to collect data from relevant literature sources. The data were analyzed qualitatively with a paradigmatic approach to achieve contextual and in-depth meaning related to the philosophical background of Passampo Siri’ and its implications for his abolition discourse. The results of the analysis show that Passampo siri’ is actually a socio-cultural entity born from the habitus of the Bugis people towards the concept of self-esteem (siri') as a core value. Removing them without a contextual understanding can threaten the integrity of the values that have been upheld and closely guarded so far. Therefore, this case reminds us of the importance of reflective attitudes and multidimensional analysis before deciding to